Aerobic training improves exercise capacity after traumatic brain injury in female, but not male, mice - Karelina, Kate; Corbin, Deborah; Gumbo, Claymore T.; Payne, Taylor; Reger, Emma; Barr, Jayden; Oldham, Mikayla; Shoemaker, Brett; Muthu, Sakthijothi; Meadows, Ethan; Hollander, John M.; Weil, Zachary M. (Frontiers in Physiology, 2025)
IntroductionTraumatic brain injury (TBI) often leads to lasting impairments in physical performance, yet its impact on aerobic function and the potential for recovery through exercise remain poorly understood. In this study, we used a well-established controlled cortical impact (CCI) model in mice to address three gaps in the preclinical TBI literature: the effect of injury on voluntary activity and energy metabolism, the extent to which exercise tolerance and cardiorespiratory fitness can be restored through moderate-intensity aerobic training, and whether these responses differ between sexes.MethodsVoluntary wheel running and metabolic outputs following CCI were quantified via the Comprehensive Lab Animal Monitoring System (CLAMS), while maximal oxygen uptake (VO2 max) and time to exhaustion were measured before and after a 10-day treadmill training regimen initiated during the subacute phase.ResultsBoth sexes displayed similar acute reductions in VO2 max following TBI; however, only females exhibited significant gains in VO2 max and exercise tolerance after exercise training, alongside higher spontaneous activity, greater energy expenditure, and smaller lesion volumes compared to males. Exercised females also exhibited selective cardiac upregulation of mitochondrial complex activity, indicating that enhanced mitochondrial capacity paralleled improved aerobic performance. In contrast, injured males showed persistent deficits and no measurable improvement in cardiovascular fitness or mitochondrial physiology from training, indicating a sex-specific limitation in aerobic adaptation.DiscussionThese findings reveal a divergence in post-TBI exercise responsiveness and highlight the need for sex-specific, physiology-guided rehabilitation strategies.